Igcse physics - Duncan, Tom; Kennett, Heather (Hodder Murray Dubai, 2002)
This international edition of GCSE Physics has been designed to provide up-to-date and comprehensive coverage of the core and supplementary topics specified in the IGCSE Physics syllabus. Amendments have been made throughout the text and the illustrations to fulfil these aims. In particular: wave theory is introduced and more details of a range of ultrasonic echo techniques such as medical ultrasound imaging are included factors affecting stopping distance are analyzed in detail and the section of satellites has been expanded volume expansion in solids, liquids and gases are compared and the term thermal capacity is explained the concept of electric fields and emf have been introduced, along with applications of potential divider circuits and the principles of ink-jet printers and magnetic recording have been added sources of background radiation hazards, nuclear stability and radioisotopes and their uses are reviewed investigations which are suitable for conection to a datalogger and computer have been identified throughout the text general advice on practical work is provided along with suggestions for more advanced investigations numerous questions from recent IGCSE examination papers have been included.